2019
DOI: 10.1007/s10661-019-7550-9
|View full text |Cite
|
Sign up to set email alerts
|

Methodological elements for optimising the spatial monitoring design to support regional benthic ecosystem assessments

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…Consequently, the big challenge is to evaluate how relevant the data is for the actual purpose. A further challenge in trans-national regional assessments is that countries might have different traditions, priorities, or resources available for monitoring (Van Hoey et al 2019). This was also reflected in this study, where the review of current monitoring programmes revealed different monitoring practices between the Baltic Sea bordering countries.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Consequently, the big challenge is to evaluate how relevant the data is for the actual purpose. A further challenge in trans-national regional assessments is that countries might have different traditions, priorities, or resources available for monitoring (Van Hoey et al 2019). This was also reflected in this study, where the review of current monitoring programmes revealed different monitoring practices between the Baltic Sea bordering countries.…”
Section: Discussionmentioning
confidence: 84%
“…Benthic communities are proficient indicators of environmental changes, as changes in the community composition reflect changes in the environment (Leppäkoski 1975;Pearson and Rosenberg 1978;Dauer 1993). To detect changes in benthic communities and provide reliable status assessments at regional scale, appropriate and welldesigned monitoring programmes are needed (Van Hoey et al 2019). In the Baltic Sea, there is a >-50-year-long tradition of monitoring soft-bottom macrofauna communities, providing unique time series to study changes over time.…”
Section: Introductionmentioning
confidence: 99%
“…Towards standardization of DNA metabarcoding for marine environmental monitoring A European scale monitoring method has been identified as a science priority need to support benthic ecosystem assessments (Van Hoey et al, 2019). Biotic indexes inferred from DNA based taxonomic assignments are comparable to indexes derived from morphological identifications (Aylagas et al, 2018;Elbrecht, Vamos, et al, 2017;Lobo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Also, these baseline data should inform the long-term design of the monitoring and assessment programme for the MPA and should highlight any knowledge gaps. These programmes should: be aligned with the conservation and operational objectives of the MPA; use appropriate indicators; be sensitive to identified stressors or management actions; and be integrated into the wider scale of regional monitoring programmes (Buhl-Mortensen et al, 2017;Loh et al, 2019;Van Hoey et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Western Mediterranean Sea was the main exception to this, because of good scores in the designation phase that were replicated for indicators and assessments in the implementation phase. A coherent and efficient spatial sampling design for the benthos in all phases is essential to achieve more accurate status assessments (Van Hoey et al, 2019).…”
mentioning
confidence: 99%